2010
DOI: 10.1007/s10787-010-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic data capture using the Womac® NRS 3.1 Index (m-Womac®): a pilot study of repeated independent remote data capture in OA

Abstract: These data support the feasibility of repeated independent remote data capture using the m-WOMAC NRS3.1 Index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Although this usability testing was conducted using subjects with OA (three of which reported also having rheumatoid arthritis), none of the subjects reported experiencing physical discomfort when using the handheld device. These findings are consistent with previously published studies demonstrating the usability of electronic data capture of PROs in patients with OA and other rheumatologic conditions 3739…”
Section: Resultssupporting
confidence: 93%
“…Although this usability testing was conducted using subjects with OA (three of which reported also having rheumatoid arthritis), none of the subjects reported experiencing physical discomfort when using the handheld device. These findings are consistent with previously published studies demonstrating the usability of electronic data capture of PROs in patients with OA and other rheumatologic conditions 3739…”
Section: Resultssupporting
confidence: 93%
“…With the growth of mobile phones, there has been more recent interest in testing a version of WOMAC on a mobile phone. Bellamy et al (Level of Evidence:4) tested a version of the mobile WOMAC index (m-WOMAC) with older adult patients (n=12), who regarded the system as easy to use (Very easy:11/12) and acceptable for use (Very confident in continued use: 11/12), with the index being transmitted successfully[48]. Other studies (n=62, n=12) found a high agreement between paper and mobile versions of the WOMAC index (Level of evidence: 4, 4; Correlation: 0.90+, 0.996), and found that the favorable reviews by participants and the effectiveness of the platform held across multiple phones[49,50].…”
Section: Resultsmentioning
confidence: 99%
“…Rule-based feedback can be combined with healthcare provider alerts and review, which in some studies were considered useful by the acting healthcare provider[24,27,34]. In addition, several studies have shown high patient acceptability of mobile systems, along with patient satisfaction of the effectiveness of the system[22,23,48]. However, many of these studies were pilot or feasibility studies with small sample sizes of older adults, and consequently need to be replicated with larger samples to generate more generalizable results and establish a higher confidence in the evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Frequently discussed problems in assessing electronic PRO data include patient age and related computer literacy [10,[21][22][23][24], as well as the additional time and burden for the patient and healthcare institutions in supplying electronic devices and giving instruction on their use [22,[25][26][27][28][29]. However, this study showed that age was not a factor.…”
Section: Discussionmentioning
confidence: 81%
“…The time required for questionnaire completion is a very important factor in outpatient clinics, and PRO assessment must not cause substantial delays or burden the patients. In 2010, Bellamy et al [25] adapted the electronic WOMAC for use on a smartphone. Their patients required less than 5 min to answer the questionnaire, although questions were presented on a small smartphone display.…”
Section: Discussionmentioning
confidence: 99%